EVALUATING FOOD QUALITY OF TUNA HOUSE MEGA MAS MANADO USING IMPORTANCE AND PERFORMANCE ANALYSIS - Mangundap, Hizkia Toar; Kindangen, Paulus .; Worang, Frederik G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract : The Food aspect has a great influence and is a significant driver in Indonesiaâ€™s economy. Tuna house is the most well-known tuna restaurant in Manado, since it is the first restaurant that made tuna fish popular. To maintain the popularity of Tuna HouseMega Mas Manado, the restaurant needs to consider abo.ut the quality of the food. This research aims to analyze and evaluate Food Quality of Tuna House Mega Mas Manado. In order to define these variables this research takes a quantitative approach by obtaining data through questionnaires using convenience sampling in which 100 customers of Tuna House Mega Mas Manado are the respondents. To analyze the data this research uses Importance and Performance Analysis as the research method. There are 4 variables included in the analysis and 5 indicators for each variable. From the results of analyzing 4 variablesthere are 2 varibles that are importance to the customers and customers feel satisfied with the performance, and those variables are taste and freshness. There are 2 variables that have low importance and performance also to the customers, and those variables are innovative food and presentation, so the restaurant can be focused on other aspects or variables.Â Keywords: foodquality, importance and performanceanalysis